Strategi Pendidikan Agama Katolik untuk Generasi Z dalam Menciptakan Kebermaknaan Spiritual di Era Digital - Yohanes Chandra Kurnia Saputra (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2025)
This research discusses Catholic religious education strategies for Generation Z in bringing spiritual meaning to the digital world. Generation Z, characterized by traits such as high-tech skills and distinct learning preferences, faces unique challenges in religious education. The development of digital technology plays a huge role in Generation Z's daily lives, with social media and digital platforms being a major influence. However, there are positive and negative impacts on spirituality and Catholic religious education. The integration of digital technology with Catholic religious education is important. This research explores digital and e-learning theories as well as successful technology integration models in the context of Catholic religious education. Effective pedagogical approaches, interactive strategies, and innovative methods are needed to teach spiritual values ​​through technology. Spiritual meaning in the digital era is the main focus. This research defines spiritual meaningfulness, highlights ways to achieve and maintain it in the digital world, and describes the role of Catholic religious education in this process. This research links religious education theory, the characteristics of Generation Z, and the development of digital technology to formulate effective educational strategies. By understanding the characteristics of Generation Z and the impact of digital technology, Catholic religious education approaches can be adapted to create meaningful learning experiences. Technology integration can be used to strengthen spiritual values ​​and support character formation. In this digital era, Catholic religious education has a vital role in helping Generation Z find and maintain spiritual meaning in their lives.